2012
DOI: 10.3892/etm.2012.819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a traditional Japanese garlic preparation on blood pressure in prehypertensive and mildly hypertensive adults

Abstract: Numerous clinical studies have used differing garlic preparations leading to controversial results with regard to the hypotensive effect of garlic. This randomized, double-blind, placebo-controlled study was designed to determine the effect of a traditional Japanese garlic homogenate-based supplementary diet (GH diet) product on blood pressure (BP) in subjects with prehypertension and in those with mild hypertension. In total, 34 eligible subjects with prehypertension and 47 with mild hypertension were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
1
16
0
2
Order By: Relevance
“…Our findings were consistent with a previous meta鈥恆nalysis by Ried and colleagues in 2008 . We believe our meta鈥恆nalysis has some advantages as it included new trials and evaluated the methodological quality of the selected trials using the nine quality criteria proposed by the Dutch Cochrane Centre in 2009 (Table). We reanalyzed the high鈥恞uality trials after the low鈥恞uality trials were removed and found that a significant reduction in both SBP and DBP still existed in the garlic鈥恡reat group.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings were consistent with a previous meta鈥恆nalysis by Ried and colleagues in 2008 . We believe our meta鈥恆nalysis has some advantages as it included new trials and evaluated the methodological quality of the selected trials using the nine quality criteria proposed by the Dutch Cochrane Centre in 2009 (Table). We reanalyzed the high鈥恞uality trials after the low鈥恞uality trials were removed and found that a significant reduction in both SBP and DBP still existed in the garlic鈥恡reat group.…”
Section: Discussionsupporting
confidence: 89%
“…Among the 17 trials, one included two separate random鈥恈ontrolled trials that involved hypertensive patients and normotensive individuals, therefore this trial was counted as two trials. Therefore, our meta鈥恆nalysis included a total of 18 trials, seven of which comprised hypertensive individuals and six normotensive individuals, another five included both hypertensive and normotensive individuals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that consumption of 300 mg/day of dehydrated garlic homogenate in subjects with mild hypertension and prehypertension lowered systolic and DBP in mild hypertension patients but not in prehypertension. The garlic homogenate diet was tolerated without any clinically significant untoward effects [69]. In a randomized study, uncontrolled hypertensive patients ingested one, two, or four capsules daily of aged garlic extract (240/480/960 mg), and blood pressure was assessed at 4, 8, and 12 weeks.…”
Section: Human Studiesmentioning
confidence: 99%